Research focus and authorship trends over 40 years of publications by New Zealand Plant Protection - Stewart, T.M. (New Zealand Plant Protection, 2016)
In total 3053 contributions consisting of papers research notes and poster abstracts to the New Zealand Plant Protection Society from 1976 to 2015 were analysed for research and authorship trends The mean number of authors per paper per year increased from 18 to 43 over this period and institutional collaboration was increasingly common Proportionally there was a steady decrease in weed contributions and an increase in those featuring plant pathogens Control measures shifted from largely chemical solutions for single weed species to more integrated management programmes The number of papers on weed pest or disease biology incidence spread and impact were fairly constant over this period The scope of research widened considerably from a largely pastoral and arable focus to include environmental weeds and border biosecurity Topical research findings and review papers highlight the responsiveness of the plant protection research community to emerging novel issues